TEACHING COMPUTER GRAPHICS AS A PEDAGOGICAL PROBLEM ON THE BASIS OF MASSIVE OPEN ONLINE COURSES IN INFORMATION CONDITIONS - Bagbekova Laylo Kadirbergenovna (Scholar Express Journal, 2022)
This article provides information on the concept of a public open online course and foreign experience in its application in the educational process, research on the current state of teaching computer graphics
Keywords: Massive; open; online; course